P3-S2.02 Variations in testing and treatment received by infants with possible neonatal herpes. (10th July 2011) - Meites, E; Xu, F; Hutchins, K; Ackerson, B; Gee, J; Eriksen, E; Naleway, A; Markowitz, L; Zangwill, K
Abstract : Background: Data are scarce on clinical care of infants with possible neonatal herpes simplex virus (HSV) infection, a rare and serious condition that should be treated with systemic acyclovir for 14–21 days. We reviewed HSV testing and treatment in a large cohort of US infants in order to assess clinical care received. Methods: We investigated >270 000 infants born from 1997 to 2002 at three managed care organizations participating in the US Vaccine Safety Datalink. Medical records were abstracted if an infant had a discharge ICD-9 code compatible with HSV infection, a positive laboratory test for HSV, or neonatal death. Abstracted data included symptoms, testing, and treatment. Two physicians reviewed likely HSV infections. We identified confirmed cases (compatible symptoms and positive laboratory test), probable cases (compatible symptoms only), and others (with an alternate diagnosis). Descriptive frequencies were calculated. Results: We abstracted records from 770 infants, identifying 35 cases (24 confirmed and 11 probable) and 735 others. HSV infection manifested as skin, eye, and mucosal (SEM) disease in 20 cases, central nervous system (CNS) disease in 8 cases, and disseminated disease in seven cases. Among 35 cases, all 35 (100%) had symptoms compatible with HSV infection; these included vesicular lesions in 20 (57%) and seizure in 7 (20%). Overall, 35 (100%) were ever tested for HSV. At least 34 (97%) received some acyclovir; median time to treatment, available for 32 cases, was 3 days (range 0–35 days). Only 8 (23%) received systemic acyclovir for the recommended 14–21 days, while 18 (51%) received <14 days and 8 (23%) received more than 21 days. Among 735 others, 701 (95%) had symptoms compatible with HSV infection; these included vesicular lesions in 10 (1%) and seizure in 244 (33%). Overall, 172 (23%) were ever tested for HSV, including 7/10 (70%) with vesicular lesions and 69/244 (28%) with seizure. At least 98 (13%) received some acyclovir, including 2/10 (20%) with vesicular lesions and 18/244 (7%) with seizure. Of these, 32 (4%) infants received acyclovir for ≥7 days. Conclusions: Our results reveal variations in clinical care of infants with possible neonatal HSV infection. Among cases, duration of antiviral therapy rarely followed treatment recommendations. Among symptomatic infants, most with vesicular lesions but few with seizures were ever tested for HSV. These variations suggest opportunities for clinical quality improvements.